Destination Image Meets Digital Promotion: Shaping Sustainable Tourist Choices at Big Farmer for Food Security - Sindrawati Sindrawati; Bachtiar Usman; Hermanto Yaputra (Westscience Press, 2026)
Tourism is widely acknowledged as a catalyst for economic development and social progress, while also serving as a strategic instrument to strengthen food security and support the achievement of the Sustainable Development Goals (SDGs). Within this scope, agro-tourism plays a critical role in connecting tourism with agricultural sustainability, providing benefits for local communities, rural economies, and environmentally responsible consumption. This study investigates the extent to which destination image and digital promotion influence visiting decisions at Big Farmer, an agro-tourism site in West Bandung, with particular attention to Generation Z as the dominant respondent group. Grounded in consumer behavior and sustainable tourism theories, the study applied a quantitative research design, using a structured questionnaire distributed to 99 respondents. Data analysis employed descriptive statistics, validity and reliability testing, as well as multiple regression through SPSS 25. Results confirm that both destination image and digital promotion significantly and positively impact visiting decisions, while Generation Z demonstrated strong responsiveness to authentic digital narratives emphasizing local food identity, cultural heritage, and sustainable practices. These findings highlight the importance of enhancing destination branding and interactive digital strategies as tools not only to improve tourism competitiveness but also to reinforce community-based food systems. The study concludes that tourism stakeholders and policymakers should prioritize digital innovation and agricultural integration in tourism promotion, ensuring that agro-tourism contributes to SDG 2 (Zero Hunger), SDG 8 (Decent Work and Economic Growth), and SDG 12 (Responsible Consumption and Production).